2021
DOI: 10.1029/2021jd034823
|View full text |Cite
|
Sign up to set email alerts
|

Convection‐Permitting Hindcasting of Diurnal Variation of Mei‐yu Rainfall Over East China With a Global Variable‐Resolution Model

Abstract: Mei-yu is a unique climatic feature associated with frontal systems during the northward propagation of the East Asian summer monsoon that produces abundant rainfall particularly in the Yangtze-Huaihe River basin (YHRB), West Japan (called Baiu), and South Korea (called Changma) (e.g., Ding, 1992;Tao & Chen, 1987). During the Mei-yu season, the western Pacific subtropical high (WPSH) is zonally aligned with the ridge extending from southern Japan to southern China. The warm and moist air transported by the Eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 85 publications
(168 reference statements)
0
13
0
Order By: Relevance
“…Upgrades to higher horizontal model resolution will allow a better representation of typhoon effects. Using high‐resolution convective permitting models for S2S TC prediction appears very promising (M. Xu et al., 2021; Risanto et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Upgrades to higher horizontal model resolution will allow a better representation of typhoon effects. Using high‐resolution convective permitting models for S2S TC prediction appears very promising (M. Xu et al., 2021; Risanto et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Its dynamical core solves a set of fully compressible non‐hydrostatic equations using the finite‐volume method, discretized horizontally on a C‐grid staggered unstructured spherical centroidal Voronoi tessellation (SCVT) (Ringler et al., 2010; Thuburn et al., 2009) and vertically in a geometric‐height hybrid terrain‐following coordinate (Klemp, 2011). MPAS‐A has been used for applications such as medium‐range convection‐permitting ensemble forecasts (Schwartz, 2019), study of spatial and temporal wind speed variability during open cellular convection (Imberger et al., 2021), diurnal variation of Mei‐yu rainfall over East China (Xu et al., 2021), investigation of western North Pacific tropical cyclone tracks and intensities (Lui et al., 2021), etc. Modifying the source code of MPAS‐A, we extend the model to cover usages where one would conventionally use WRF with domain nesting for high‐resolution simulations around a region of interest.…”
Section: Model and Static Input Datamentioning
confidence: 99%
“…Jeworrek et al (2021) revealed that the GF scheme performed better for summertime convective precipitation, but the KF parameterization better simulated wintertime frontal precipitation over the complex terrain of southwest British Columbia. Furthermore, previous studies have also pointed out that simulations with convective parameterizations exhibited large deficiencies in capturing precipitation intensity and frequency and failed to reproduce the diurnal variation of heavy precipitation (e.g., Dai 2006, Stephens et al 2010, Lin et al 2017, Xu et al 2021. For instance, Li et al (2020) found that the simulation with convective parameterization underestimated the entire warm-season precipitation intensity during the East Asian summer monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that increasing grid horizontal resolution could significantly improve the capability to simulate extreme precipitation because the impacts of topography, land use, and other important processes are better resolved (Bacmeister et al 2014, Prein et al 2015. For weather prediction, many studies have shown that when the model resolution increases to convection-permitting scale, the spatial and temporal distributions, diurnal variations, and intensity of precipitation can be predicted more accurately (Zhu et al 2018, Zhao et al 2019, Xu et al 2021. Zhu et al (2018) indicated that the convection-permitting forecasts of precipitation in China during the summer of 2013-2014 outperform global forecasts in terms of spatial distribution, intensity, and diurnal variation.…”
Section: Introductionmentioning
confidence: 99%